2021
DOI: 10.1007/s10549-021-06343-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between MRI morphological response patterns and histopathological tumor regression after neoadjuvant endocrine therapy in locally advanced breast cancer: a randomized phase II trial

Abstract: Purpose To correlate MRI morphological response patterns with histopathological tumor regression grading system based on tumor cellularity in locally advanced breast cancer (LABC)-treated neoadjuvant with third-generation aromatase inhibitors. Methods Fifty postmenopausal patients with ER-positive/HER-2-negative LABC treated with neoadjuvant letrozole and exemestane given sequentially in an intra-patient cross-over regimen for at least 4 months with MRI re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 34 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…The classification and definition of TSP at MRI have not been consistently recognized and unified. The CS or non-CS patterns after NAT and further refinement of non-CS pattern at mid-NAT were commonly used [ 11 , 17 , 20 ]. Based on Fukada et al’s study [ 11 ], we developed four-category TSP and subdivided CS and DD pattern to suit early NAT response.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The classification and definition of TSP at MRI have not been consistently recognized and unified. The CS or non-CS patterns after NAT and further refinement of non-CS pattern at mid-NAT were commonly used [ 11 , 17 , 20 ]. Based on Fukada et al’s study [ 11 ], we developed four-category TSP and subdivided CS and DD pattern to suit early NAT response.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the DD pattern after early NAT tended toward pCR in HR + /HER2 − subtype, mainly at 1st-timepoint, independent of size change. Reis et al [ 20 ] reported that early fragmentation pattern after 2 months neoadjuvant endocrine therapy suggested effective treatment in ER + /HER2 − subtype. The DD pattern may be the early manifestation of HR + /HER2 − subtype response to NAT earlier than size reduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tumour shrinking pattern was de ned as tumour regression on MRI compared to that at baseline after two courses of NST. Tumour regression was classi ed into 6 categories [9]: 0 (complete imaging response), I (concentric shrinkage), II (fragmentation), III (diffuse contrast enhancement), IV (stable disease), and V (progressive disease). The preoperative MRI residual tumour status was de ned as the evaluation of the presence of a tumour based on MRI after treatment completion.…”
Section: Image Analysismentioning
confidence: 99%
“…Preoperative neoadjuvant chemotherapy can allow some patients to regain the opportunity for surgery and reduce tumor staging in some patients (4). However, tumor regression following chemotherapy can be a concern, as the remaining tumor cells cannot be located even under a microscope in some patients (5). Moreover, illness assessment focuses on axillary lymph node examination after treatment (6).…”
Section: Introductionmentioning
confidence: 99%